2018
DOI: 10.1111/ejh.13024
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism and gene therapy — Lessons learned from non‐conditioned murine bone marrow transplantation models

Abstract: By extrapolating our murine data, and data from some previous studies to a human non-conditioned autologous CD34 HSPC transplantation setting, we conclude that approximately 44 million CD34 HSPCs would be needed to achieve 20% donor chimerism in a 70-kg human, which could serve as a starting point for the future use of HSCPs in gene and cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These phenomena are similar to clinical GVHD symptoms and signs including dry eye, myalgia, asthenia, and change in fur characteristics 28 . These findings clearly demonstrated that the mouse model of allogeneic BMT is an ideal tool to explore the pathogenesis of GVHD 10 .…”
Section: By Fcm Through An Incubation With Fitc-conjugated Anti-h-2k ...mentioning
confidence: 72%
See 1 more Smart Citation
“…These phenomena are similar to clinical GVHD symptoms and signs including dry eye, myalgia, asthenia, and change in fur characteristics 28 . These findings clearly demonstrated that the mouse model of allogeneic BMT is an ideal tool to explore the pathogenesis of GVHD 10 .…”
Section: By Fcm Through An Incubation With Fitc-conjugated Anti-h-2k ...mentioning
confidence: 72%
“…BMT can create a permanently chimeric individual containing original diseased cells and newly transplanted healthy cells that convey a therapeutic effect in the form of a healthy gene. The level of chimerism can effectively evaluate the occurrence of moderate to severe aGVHD after transplantation 10 . Monitoring variations in cell chimerism early after transplantation help to identify patients at risk for graft rejection or grade II-IV aGVHD 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, we have recently shown in an animal model that the non-conditioned haHSCT leads to a stable chimerism in the bone marrow HSCs as well as in the myeloid and lymphoid progenitor subpopulations of the recipient, clearly showing a linear dose-dependent response. Extrapolating these results to the human setting, we found that approximately 44 million CD34+ HSCs would be needed to achieve 20% donor chimerism in a 70-kg human, which is probably sufficient for a substantial replacement of aged HSCs (Jazbec et al 2018).…”
Section: What Could Be Expected From Heterochronous Autologous Hematopoietic Stem Cell Transplantation?mentioning
confidence: 86%
“…Since a completely autologous setting is practically unattainable in mice due to the scarcity of biological materials of an individual mouse, we used a syngeneic heterosexual donor/recipient combination to closely mimic the autologous tissue compatibility setting [15][16][17]. Old female BALB/c mice as recipients, and young inbred BALB/c males as donors were also chosen for enabling precise determination of the post-transplantation mixed chimerism, based on the presence of the Y chromosome, as already set in our previous studies [18,19]. Similarly, since the isolation of large numbers of pure HSCs from young mice needed for consequent long-term cryopreservation and transplantation is practically impossible, HSCT was substituted by transplantation of the whole BM of young donors.…”
Section: Introductionmentioning
confidence: 99%